A Review Paper on Static and Dynamic Analysis Using Staad Pro - Aman Pandey; Anita Chaturvedi; Pradeep Kumar Nirmal (International Journal of Scientific Research in Civil Engineering, 2025)
For multi-story structures to remain safe, stable, and structurally sound under a range of loading scenarios, analysis is crucial. In order to assess the structural behavior of a G+4 (Ground plus Four) storey building in terms of bending moment, shear force, axial force, and torsion, this study does both dynamic and static analysis. The study highlights the differences in these forces under various loading circumstances by comparing the findings from both dynamic and static analytical approaches. Important factors for assessing the overall performance of the building structure are the bending moment, shear force, axial force, and torsion. Shear forces give information on how forces are transmitted through the structural parts, whereas bending moments are calculated to evaluate the building's flexural behavior under load.
Keywords: Earthquake resistant building; Shear wall; Seismic analysis; Structural engineering